2021
DOI: 10.3390/ijerph18105261
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Narratives about COVID-19, Preventive Practices and Sources of Information in Northwestern Tanzania

Abstract: COVID-19 has affected millions of people across the world. We conducted a phone based qualitative study to explore women’s perceptions of COVID-19, knowledge of its symptoms, transmission, and prevention practices in Northwestern Tanzania. We also examined their sources of information about the disease. Findings show that much of women’s framing of etiology, symptoms, and transmission routes of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) greatly reflects the World Health Organization (WHO)/Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(28 reference statements)
2
9
0
Order By: Relevance
“…We collected data using interviews carried out in person or through virtual platforms, allowing our team to conduct the study during the Covid-19 outbreak in Tanzania. This is in line with a recent study conducted by our team [ 54 ], which showed that using virtual platforms and mobile phones for data collection during restrictions related to the Covid-19 pandemic enhanced safety for both the research team and the study participants, as well as saving time and cost for travel.…”
Section: Discussionsupporting
confidence: 90%
“…We collected data using interviews carried out in person or through virtual platforms, allowing our team to conduct the study during the Covid-19 outbreak in Tanzania. This is in line with a recent study conducted by our team [ 54 ], which showed that using virtual platforms and mobile phones for data collection during restrictions related to the Covid-19 pandemic enhanced safety for both the research team and the study participants, as well as saving time and cost for travel.…”
Section: Discussionsupporting
confidence: 90%
“…Because the disease did not officially exist in the country, general treatment guidelines were never released, and every hospital had to rely on their own protocols to handle patients with COVID-19. The government's stance also changed the public's perception of COVID-19 and undermined their trust in conventional medicine (Buguzi, 2021;Mchome et al, 2021). Additionally, Verelst et al (2018) discovered that people are less incentivised to get vaccinated as the prevalence of the vaccine preventable disease seemingly drops, and Hornsey et al (2020) found that people tended to be significantly more concerned about vaccines after being exposed to anti-vax tweets from former US president Trump.…”
Section: The Tanzanian Contextmentioning
confidence: 99%
“… 28 A small qualitive study of women (without cancer) in Tanzania found that they many had ‘normalised’ COVID-19 as an illness such as seasonal malaria or influenza, and some believed that God had answered their prayers in protecting Tanzania against COVID-19. 29 While the study did not compare women with men, a possible interpretation is that women were more likely than men to believe these narratives which were circulated by the government and media.…”
Section: Discussionmentioning
confidence: 97%
“…This contrasts to studies in Italy and Poland, where female patients with cancer were more likely to fear COVID-19 than male patients with cancer22 27 and a recent meta-analysis which found that in general populations, women had greater COVID-19 related fear and anxiety 28. A small qualitive study of women (without cancer) in Tanzania found that they many had ‘normalised’ COVID-19 as an illness such as seasonal malaria or influenza, and some believed that God had answered their prayers in protecting Tanzania against COVID-19 29. While the study did not compare women with men, a possible interpretation is that women were more likely than men to believe these narratives which were circulated by the government and media.…”
Section: Discussionmentioning
confidence: 99%